2022
DOI: 10.1155/2022/9103259
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognosis Signature Based on Ferroptosis-Related Gene DNA Methylation Data for Lung Squamous Cell Carcinoma

Abstract: Ferroptosis-related genes regulating an iron- and lipid reactive oxygen species (ROS)-dependent form of programmed cell death suggest critical roles for ferroptosis in cancers. However, the prognostic value of ferroptosis-related epigenetic features such as DNA methylation in lung squamous cell carcinoma (LUSC) needs to be studied. Ferroptosis-related genes are collected from the FerrDb database, and the methylation data of these related genes in LUSC methylation data downloaded from the TCGA are retrieved. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Recent data from The Cancer Genome Atlas (TCGA) show that multiple ferroptosis-related genes are dysregulated in cancer, which may be related to aberrant DNA methylation [94]. Overexpression of SLC7A11, a transporter protein that inputs cysteine for the biosynthesis of glutathione and causes antioxidant defense, inhibits ferroptosis and promotes tumor growth [64, protein methylation and ACSL4 degradation, and ultimately inhibits the ferroptosis of GC cells, enhances chemoresistance and affects prognosis [98].…”
Section: Epigenetic Modifications In Ferroptosismentioning
confidence: 99%
“…Recent data from The Cancer Genome Atlas (TCGA) show that multiple ferroptosis-related genes are dysregulated in cancer, which may be related to aberrant DNA methylation [94]. Overexpression of SLC7A11, a transporter protein that inputs cysteine for the biosynthesis of glutathione and causes antioxidant defense, inhibits ferroptosis and promotes tumor growth [64, protein methylation and ACSL4 degradation, and ultimately inhibits the ferroptosis of GC cells, enhances chemoresistance and affects prognosis [98].…”
Section: Epigenetic Modifications In Ferroptosismentioning
confidence: 99%
“…They further established the ferroptosis potential index (FPI) and found that, compared with normal tissues, most cancer cells were characterized with a high FPI and that a high FPI predicted poor prognosis for several tumors [108]. Similarly, many ferroptosisassociated DNA methylation signatures have been developed to predict the prognosis for various tumors, such as glioblastoma multiforme (GBM), head and neck squamous cell carcinoma (HNSCC), cutaneous melanoma (CM), and lung squamous cell carcinoma (LUSC) [109][110][111][112]. DNA methylation of FRGs is involved in the regulation of their expression.…”
Section: Dna Methylation In Ferroptosismentioning
confidence: 99%
“…DNA methylation of FRGs is involved in the regulation of their expression. For instance, analyzing the most recent TCGA multidimensional omics data revealed that multiple iron-related genes ( e.g., scavenger receptor class A member 5 (SCARA5), erythroferrone (ERFE), lipocalin 2, transferrin receptor 2 (TFR2), solute carrier family 11 member 1 (SLC11A1), and cytochrome B reductase 1 (CYBRD1)) were dysregulated in different cancers, and this outcomes may be associated with aberrant DNA methylation 112 . Hypomethylation of the epigenome and increased TET1 expression have been observed in colonocytes subjected to continuous iron exposure 113 .…”
Section: Dna Methylation In Ferroptosismentioning
confidence: 99%